2010
DOI: 10.1182/blood-2010-05-284448
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin-heparin covalent complex reduces microemboli during cardiopulmonary bypass in a pig model

Abstract: Transcranial Doppler-detected high-intensity transient signals (HITS) during cardiopulmonary bypass (CPB) surgery have been associated with postoperative neurocognitive dysfunction, suggesting microemboli in the brain could be a contributing factor. HITS occur despite administration of unfractionated heparin (UFH). This study was done to determine whether antithrombin-heparin covalent complex (ATH), a more potent anticoagulant than heparin, can reduce HITS during CPB. In a pig CPB model, ATH, UFH, or UFH ؉ ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Hemocompatibility could be achieved by surface modification with anticoagulants such as antithrombin-heparin (ATH) complex (34,35). In this study we present preliminary data about our progress in determining where surface treatment is required in SOUs.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocompatibility could be achieved by surface modification with anticoagulants such as antithrombin-heparin (ATH) complex (34,35). In this study we present preliminary data about our progress in determining where surface treatment is required in SOUs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite heparin use, microemboli formation still poses a problem during and after CPB surgery (85). Transcranial Doppler monitoring has been used to detect microemboli as high-intensity transient signals (HITS) during CPB.…”
Section: Cardiac Surgery With Cardiopulmonary Bypassmentioning
confidence: 99%
“…To overcome some of the limitations of UFH, our laboratory has developed a covalent complex of antithrombin and heparin (ATH) with high anticoagulant activity (25). Numerous in vitro and in vivo investigations involving ATH have led to results showing potential clinical advantages of ATH over UFH (25)(26)(27)(28)(29)(30). More specifically, we have demonstrated that ATH inhibits FXa within a prothrombinase on an artificial phospholipid surface much better than AT+UFH (24).…”
Section: Introductionmentioning
confidence: 99%